Conceptualizing research and innovation: Issues and implications for Higher Education Research and Publications in Africa - Barasa, Fred Simiyu (Kabarak University, 2014)
The quest for change, improvement and competitiveness characterize individual, institutional and state endeavours in today's world. This is largely because globalization and liberalization of the world economy has presented both opportunities and challenges to political leaders, providers of education and training services, recipients of those services, as well as other individuals and social groups. Among opportunities created by a globalized and liberalized world economy, underpinned by rapid technological developments, are an expanded market for goods, services and skills; a more efficient and cheaper system of transport and communications which promotes the volume and pace of information flow across national and disciplinary boundaries; and an environment that demands continuous adaptation and innovation thereby reinforcing the need for a culture that embraces creativity, cutting-edge research and lifelong learning as its important elements. However, these opportunities translate into numerous challenges and varying degrees of anxiety among various players in both developed and developing countries. Lee (1996) has identified four sources of anxiety over the effects of globalization. First, globalization unleashes new international competition from newly industrialized countries against established economies. This leads to rising unemployment and a fall in relative wages among unskilled workers. Second, it is feared among developing countries (and rightly so) that liberalization has and will progressively continue leading to job losses and rising wage inequality. Third, globalization of labour markets erodes wages and labour standards. Fourth, globalization leads to a loss of national policy autonomy, and renders governments especially in developing economies, impotent.
Keywords: Research; Innovation; higher education; globalization; Africa; issues